Fungal genes in the innovation and evolution of land plants - Wang, Shuanghua (Plant Signal Behav, 2021)
Although fungal association has been instrumental to the evolution of land plants, how genes of fungal origin might have contributed to major plant innovations remains unclear. In a recent study, we showed that a macro2 domain-containing gene likely acquired from mycorrhiza-like fungi is important in gametophore development of mosses, suggesting a role of fungi-derived genes in the three-dimensional growth of land plants.